Dreams as reinforcing stimulus in emily jane bronte’s gothic romance (2022)
Dreams and interpretation of dreams are elements that have been subjected to psychological, neuroscientific and religious examination. Dreaming, a common experience, is shared by mankind irrespective of race, gender or social indices and has been identified even in species amongst mammals. This study is concerned with the significance of dreams as reinforcing stimuli in literary texts. It explores the category of dreams that are yet to be dreamt but are explored as reinforcing stimuli in Emily Bronte's Wuthering Heights. These dreams which are mental creations of creative writers are attributed to characters invented for the purpose o f a story or a narrative technique. Brontes engagement of the dream concept and dream interpretation in constructing the plot, the structure and characterisation in Wuthering Heights is also a concern of this paper. It is observed that they embody dominant literary and archetypal elements with universal appeal. Dream visions in Emily Bronte's gothic romance portray hidden psychological and emotional patterns of individuals which recur while dreaming. Taking bearingfrom Freudian perspectives, dream analysis in literary texts reveals depths of buried memories in a manner that they can be explicated.